2013
DOI: 10.1371/journal.pone.0054596
|View full text |Cite
|
Sign up to set email alerts
|

Two Panels of Plasma MicroRNAs as Non-Invasive Biomarkers for Prediction of Recurrence in Resectable NSCLC

Abstract: The diagnosis of non-small cell lung carcinoma (NSCLC) at an early stage, as well as better prediction of outcome remains clinically challenging due to the lack of specific and robust non-invasive markers. The discovery of microRNAs (miRNAs), particularly those found in the bloodstream, has opened up new perspectives for tumor diagnosis and prognosis. The aim of our study was to determine whether expression profiles of specific miRNAs in plasma could accurately discriminate between NSCLC patients and controls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(155 citation statements)
references
References 48 publications
2
151
0
2
Order By: Relevance
“…This may be due to the breakdown of the miRNA in the plasma samples. However, the majority of the previous studies in NSCLC did not examine the exosomal miRNAs separated from the plasma or serum, which would likely include the intact miRNA (7)(8)(9)(10)(11)(12)(13)(26)(27)(28)(29). In the present study, microarray-based expression profiling of miRNAs derived from exosomes in the plasma of 6 NSCLC patients with or without recurrence was employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the breakdown of the miRNA in the plasma samples. However, the majority of the previous studies in NSCLC did not examine the exosomal miRNAs separated from the plasma or serum, which would likely include the intact miRNA (7)(8)(9)(10)(11)(12)(13)(26)(27)(28)(29). In the present study, microarray-based expression profiling of miRNAs derived from exosomes in the plasma of 6 NSCLC patients with or without recurrence was employed.…”
Section: Discussionmentioning
confidence: 99%
“…Sanfiorenzo et al showed the importance of the two panels of plasma miRNAs for the prediction of recurrence in NSCLC patients (28). The study reported that one miRNA panel (high miR-155-5p, high miR-223-3p and low miR-126a-3p) was significantly associated with a higher progression risk in adenocarcinoma patients, and that another miRNA panel (high miR-20a-5p, low miR-152-3p and low miR-199a-5p) was significant in the prediction of likely survival rates of squamous cell carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to mRNAs and proteins, miRNAs are not involved in complex post-transcriptional and post-transcriptional modification. Considering the limitations of condition and time for tissue sampling (Freidin et al 2012), circulating miRNAs are optimal prog- nostic biomarkers for cancer (Sanfiorenzo et al 2013;Chen et al 2013b;Lin et al 2013;Greenberg et al 2013;Kim et al 2013). However, further studies should be conducted before miRNA can be extensively used in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The unique expression profile of circulating miRNA may function as the fingerprint of different diseases because miRNAs are highly stable in serum and plasma (Chen et al 2008). Circulating miRNA has been considered as a potential non-invasive biomarker in tumor diagnosis and prognosis (Sanfiorenzo et al 2013;Chen et al 2013b;Lin et al 2013;Greenberg et al 2013;Kim et al 2013;Rani et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Microarray-based studies have identified a large number of differentially expressed miRNAs in primary fibroblasts and lung tissue from patients with COPD [40][41][42]. Many of the miRNAs implicated in COPD have also been associated with various cancers, whereas miRNA that discriminated COPD from lung cancer have also been identified, including miRNAs 26a, 641, 383, 940, 662, 92a, 369-5p, and 636 [43] and miRNAs 20a, 24, 25, 152, 145, 199a [43]. Reduced expression of miR-199a-5p was reported in regulatory T cells from patients with COPD.…”
Section: Microrna-silencing Rnamentioning
confidence: 99%